Safety And Efficacy Of Antipsychotics In Schizophrenic Patients Visiting A Tertiary Care Teaching Hospital In Warangal: A Comparative Study - Naseer, Safiya; Koppolu, Manasa Sowmya; Sheshagiri, Sharvana Bhava Bandaru; Voorugonda, Sneha Priya; Eggadi, Venkateshwarlu; Gunda, Lavanya; Arumugam, Kottai Muthu (Journal of Neonatal Surgery, 2025)
The objective of present study is to compare the safety and efficacy of Antipsychotics in Schizophrenic patients by using Simpson Angus Score (SAS) and Positive and Negative Syndrome Score (PANSS). Method: It is a Prospective, observational comparative multicentric study conducted in patients diagnosed with Schizophrenia in Warangal, Telangana state. The study protocol, Data collection sheet were submitted. A total of 513 patients were screened for the study prescribed with Risperidone, Olanzapine, Amisulpride, Lurasidone, Aripiprazole. Statistical Analysis: All the parameters were expressed as graphs and data analysis was performed using MS EXCEL and Graph pad prism 9.2.0 Version. Paired t test was computed for study variables. Results: The results were confirmed by comparing the safety and efficacy of antipsychotics (Risperidone, Olanzapine, Amisulpride, Lurasidone, Aripiprazole) by using PANSS and SAS scale. Efficacy in reducing Positive and Negative symptoms severity was slightly high in Lurasidone and Aripiprazole than compared to Olanzapine, Risperidone, Amisulpride. Safety of Lurasidone and Aripiprazole was slightly more compared to Olanzapine, Risperidone and Amisulpride.